Associations between maternal urinary isoflavone concentrations and anogenital distance of offspring throughout infancy: a prospective cohort study. Issue 2 (4th November 2022) - Chen, Yao; Liang, Hong; Ji, Honglei; Sun, Xiaowei; He, Gengsheng; Wang, Yan; Dai, Wentao; Miao, Maohua; Yuan, Wei
Abstract: STUDY QUESTION: Are maternal urinary isoflavone (ISO) concentrations during pregnancy associated with anogenital distance (AGD) in infants at birth, and at 6 and 12 months of age? SUMMARY ANSWER: Higher maternal urinary ISO concentrations during pregnancy were associated with longer AGD in infants of both sexes, and equol (EQU) and daidzein (DAD) were identified as the important ISO mixture components in the observed associations. WHAT IS KNOWN ALREADY: Evidence of the association of prenatal exposure to ISO with offspring's AGD is mainly derived from animal studies, which used different study designs and had inconsistent results. Only one human study has been reported and it found null associations between maternal ISO exposure during pregnancy and AGD among boys at birth, with a small sample size and a wide range of exposure windows. No human study on girls was found. STUDY DESIGN, SIZE, DURATION: Prospective cohort study (Shanghai-Minhang Birth Cohort Study), with pregnant women recruited at 12–16 weeks of gestation in Shanghai, China between April and December 2012. One thousand two hundred and twenty-five live singletons were left in the cohort at delivery of which 480 mother–infant pairs had data on both maternal urinary ISO concentrations and at least one AGD measurement and were included in the present study. Anopenile distance (AGDAP ) and anoscrotal distance (AGDAS ) of boys and anoclitoral distance (AGDAC ) and anofourchette distance (AGDAF ) of girls were measured at birth and at 6 and 12 months of age. PARTICIPANTS/MATERIALS, SETTING, METHODS: Multiple linear regression models were used to examine the associations between maternal ISO concentrations and AGD. Bayesian kernel machine regression (BKMR) was implemented to examine both the overall effects of ISO mixture and the single effect of each ISO and identify important components of ISO mixture. MAIN RESULTS AND THE ROLE OF CHANCE: A general profile of higher concentrations of maternal ISO associated with longer AGD in infants of both sexes was observed, when maternal education, parity, BMI before pregnancy (BMI, categorical variable), passive smoking during early pregnancy, age at delivery, gestational weeks and infant body size were adjusted for. Among boys, EQU was associated with increased AGDAS at birth and at 6 and 12 months, and DAD was associated with increased AGDAP at birth. Among girls, the associations of EQU and DAD with increased AGDAC and AGDAF at birth were found. When gestational weight gain and feeding patterns of infants in the first 6 months were additionally adjusted for, and maternal BMI was adjusted for as a continuous variable, more pronounced associations were observed, especially for associations of genistein (GEN), DAD and glycitein (GLY) with increased AGDAP and AGDAS at 6 months in boys. However, these associations were not always observed in the highest tertile group, and no consistent dose–response relationships were found. Similar results were observed in BKMR models, showing positive correlations of concentration of ISO mixture with increased AGDAS at both 6 and 12 months among boys, and increased AGDAC and AGDAF at birth among girls. Statistically significant increments of 4.96 mm (95% credible interval (CrI): 1.40, 8.52) and 1.07 mm (95% CrI: 0.02, 2.13) in AGDAS at 6 months among boys and AGDAC at birth among girls, respectively, were observed at the 75th percentile of ISO mixture, compared with 25th percentile. EQU and DAD were identified as the important components among ISO-AGD associations. LIMITATIONS, REASONS FOR CAUTION: First, due to the short half-lives of ISO, the accuracy of a single spot urine sample reflecting ISO exposure during pregnancy may be limited, and thus may cause non-differential misclassification. Second, despite the adjustments for several important covariates in the study, unmeasured and residual confounding factors may remain a concern. Third, false discovery due to multiple testing may remain. Finally, the reduced sample sizes attributed to the loss of follow-up and missing data of confounders may limit our ability to detect an association, if any existed. WIDER IMPLICATIONS OF THE FINDINGS: Prenatal ISO exposure may affect the reproductive development of offspring. As ISO can be widely detected in pregnant women, especially in Eastern countries, more studies are warranted to provide evidence of the effects of prenatal ISO exposure on long-term reproductive outcomes. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by grants from the National Key Research and Development Program of China (2021YFC2701003), the National Natural Science Foundation of China (22076123), the Science and Technology Commission of Shanghai Municipality (21ZR1454700 and 20ZR1448000), the Shanghai Municipal Health Commission (20194Y0160) and Innovation-oriented Science and Technology Grant from NHC Key Laboratory of Reproduction Regulation (CX2022-04). The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.